Hegemonic masculinities in two comic films in Malayalam: Meesa Madhavan e Rajamanikyam (ArtCultura, 2016)
This paper interrogates how the films evoke a specific notion of masculinity, and valorise normative male ideals - aggression, violence, and a gendered division of space and labour. Violence and dominance are legitimised and constructed as "natural" of the male "will to power". The paper also evaluates the populist appeal of the film as a reaction against attempts to inscribe a "new man" into the paradigms of gender - the proletarian heroes are traditional male supremacists who dichotomise public and private domains and discipline women to function within the norms of family. Further, it analyses the semiotics of film that work collaboratively to create the masculine image. keywords: Malayalam cinema; masculinity; gendered violence.